Sustainability transitions and potential naturalization risk in the trade and cultivation of Selaginella kraussiana in tropical Indonesia - AHMAD DWI SETYAWAN; SUTARNO SUTARNO; SUGIYARTO SUGIYARTO; SUNARTO SUNARTO; DIANTI DIANTI (Smujo International, 2025)
Abstract. Setyawan AD, Sutarno, Sugiyarto, Sunarto, Dianti. 2025. Sustainability transitions and potential naturalization risk in the trade and cultivation of Selaginella kraussiana in tropical Indonesia. Asian J Agric 9: 925-945. Selaginella kraussiana has recently become popular as a tropical ornamental plant in Indonesia because of its attractive morphology, rapid vegetative growth, and suitability for humid shaded environments. However, information regarding the multidimensional sustainability of its cultivation and trade systems remains limited, particularly concerning ecological resilience, socio-economic performance, and potential naturalization risk associated with ornamental dissemination. This study evaluated the sustainability of S. kraussiana cultivation and trade systems in Central Java, Indonesia, using a RAPFISH-based multidimensional framework integrated with SWOT-TOWS analysis. Primary data were collected through semi-structured interviews, field observations, and environmental assessments involving 40 ornamental plant farmers and traders. Sustainability evaluation included ecological, economic, social, technological, and institutional dimensions. The ecological dimension achieved the highest sustainability index (83.93%), indicating highly sustainable cultivation conditions supported by humid microclimates and vegetative propagation systems. Economic sustainability was categorized as moderately sustainable (58.29%), whereas social sustainability remained low sustainable (36.70%). Technological and institutional dimensions showed unsustainable conditions (18.29%) due to limited innovation, weak institutional support, and low organizational integration. Monte Carlo validation confirmed strong RAPFISH ordination reliability with stress values below 0.25 and coefficients of determination (R²) above 0.94. The study indicates that increasing ornamental trade and repeated movement of vegetative planting materials may elevate propagule pressure and warrant precautionary ecological monitoring under favorable humid tropical environments. These findings highlight the urgent need for integrating ecological precaution, technological adaptation, institutional strengthening, and biodiversity conservation into sustainable tropical ornamental horticulture systems while minimizing potential ecological risks associated with ornamental dissemination.